The Current Status and Factors Associated With Implanon Service Provision by the Health Extension Workers at the Health Post Level, Wolaita Zone, Southern Ethiopia: A Cross-Sectional Study - Ketsela Desalegn; Eskindir Loha; Mengistu Meskele (Tehran University of Medical Sciences, 2017)
Objective: Family Planning is often taken as one of the "Magic Bullet" interventions owing to its high impact and wide reaching nature in achieving multiple goals. This study aimed   to assess the current status and the factors associated with health post level Implanon service provision through trained health extension workers in Wolaita zone, southern Ethiopia. Materials and methods: A cross sectional study was conducted among trained health extension workers in Wolaita zone in February 2013.  A simple random sampling technique was used to identify a total of 285 trained HEWs. First bivariate, then  multivariate logistic regression model along with 95% confidence interval was used to see the independent effect of factors associated with  current Implanon service provision by the health extension workers. Results: Currently, the number of Implaon providing trained health extension workers in Wolaita was 264(45.8%).  Distance of health post from district health offices and health center, turnover of trained health extension workers in the health post, interest of trained health extension workers in providing Implanon and their job satisfaction to serve as a health extension workers and availability of service delivery guidelines and teaching aids were associated with the current provision of Implanon by health extension workers. Conclusion: Implanon provision among trained health extension workers was affected by different factors. Hence, improving the working conditions of trained   health extension workers, regular and periodic facilitative supervision, availing service delivery guidelines and improvement of health management information system are recommended.